Efficient Synthesis of Pyrido[3,2-c]coumarins via Silver Nitrate Catalyzed Cycloisomerization and Application to the First Synthesis of Polyneomarline C - Yoon, Jeong A; Han, Young Taek (Synthesis, 2019)
Herein, we report an efficient method for the synthesis of the pyrido[3,2-c]coumarin scaffold, one of the privileged heterocycle-fused coumarin scaffolds, via a AgNO3-catalyzed cycloisomerization of 4-(propynylamino)coumarins obtained from diverse 4-hydroxycoumarins. This concise method affords pyrido[3,2-c]coumarin analogues bearing diverse substituents on the benzene or pyridine ring in moderate to good yields. Moreover, this methodology was extended to the facile synthesis of polyneomarline C, a natural pyrido[3,2-c]coumarin derivative isolated from the Chinese herbal medicine Polyalthia nemoralis A. DC., in three steps and in 26% overall yield from the known 4-hydroxycoumarin.
Keywords: cycloisomerization; pyrido[3,2-c]coumarin; polyneomarline C; heterocycle-fused coumarin; propargylamine